Historical realities in the “Idegei” dastan - Iskhakov D.M. (Золотоордынское обозрение)
Purpose of the study: To reveal the importance of studying the dastan “Idegei” from the point of view of establishing the volume and nature of the historical information contained in it. Research materials: Texts of the dastan “Idegei” with an emphasis on the Tatar versions of this epic work, including with special attention, first of all, to its national version, created through the efforts of Tatar folklorists and based on a number of oral and written versions (Siberian-Tatar, Crimean, Volga-Ural) of the dastan. Results and scientific novelty: A systematic study of the plots of the dastan, containing a reflection of historical realities, made it possible to identify in it materials on the socio-political structure of the late Golden Horde, establish its connection with specific clans, clarify in general the issue of the Tatar stratum of the state, and deal with the symbolic “birds” and “golden throne”, as well as three designations of the Ulus of Jochi (Altyn Urda, Ak Urda, Boz Urda). On this basis, it became possible to gain a deeper understanding of the characteristics of the historical consciousness of representatives of the state-forming Tatar class of the Ulus of Jochi at the stage of its beginning collapse.